Adiponectin profile at baseline is correlated to progression and severity of multiple sclerosis. (27th November 2018) - Signoriello, E.; Lus, G.; Polito, R.; Casertano, S.; Scudiero, O.; Coletta, M.; Monaco, M. L.; Rossi, F.; Nigro, E.; Daniele, A.
Abstract : Background and purpose: Adiponectin is a cytokine linking energy metabolism and immune system. After being assembled, adiponectin circulates as oligomers of different molecular weight, i.e. low, medium and high (HMW) molecular weight. These have the most potent biological effects. Multiple sclerosis (MS) is an autoimmune disease of the human central nervous system. The aim of this study was to characterize the expression levels of both total adiponectin and its oligomerization state in the serum from 99 patients with MS at baseline (i.e. not influenced by therapies). We also investigated the potential relationships between adiponectin and disease progression and severity. Methods: Adiponectin was quantified and visualized by enzyme‐linked immunosorbent assay, western blotting and fast protein liquid chromatography. During the follow‐up (3.6 ± 2.20 years), the patients were evaluated using total annualized relapse rate and Expanded Disability Status Scale score. Results: Total adiponectin is statistically higher in patients with MS compared with matched controls (12.18 vs. 10.02 μg/mL, P  =   0.001). Interestingly, the adiponectin oligomerization state is altered in MS, with an increase of HMW oligomers. In addition, patients with MS with higher levels of adiponectin at baseline have significantly higher risk of progression and severity (Multiple Sclerosis Severity Score, 3.84 vs. 2.44, P  =   0.001). No statistical difference in adiponectin expression was found between active and inactive patients with MS and among the different forms of disease. Conclusions: This study demonstrated that adiponectin and its HMW oligomers are greatly involved in MS autoimmune disorder representing a potential biomarker to predict worse MS prognosis and severity. Further studies are required to clarify the molecular mechanisms underlying the properties of adiponectin and HMW oligomers in MS.